2016
DOI: 10.1097/dbp.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Sleep Patterns in Toddlers Born Preterm

Abstract: Objective Children born preterm are at elevated risk for several developmental and health concerns. Early sleep patterns may be associated with these concerns. The current study assesses the associations between toddler circadian sleep/activity patterns and later developmental, behavioral, attentional, and health concerns in this at-risk population. Methods We examined circadian sleep/activity patterns at 2 years of age in 99 children born preterm. Child cognitive skills were tested at 3 years of age, and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Skeldon, Derks and Dijk [23] has previously found that sleep patterns in late childhood (age 10+) corresponded with a higher μ . Changes in ν νc have already been suggested in the literature [30-32], and in particular McGraw, Hoffmann, Harker and Herman [25] and Jenni, Deboer and Achermann [24] showed that the circadian rhythm in sleep is non-existent in the days soon after birth.…”
Section: Resultsmentioning
confidence: 93%
“…Skeldon, Derks and Dijk [23] has previously found that sleep patterns in late childhood (age 10+) corresponded with a higher μ . Changes in ν νc have already been suggested in the literature [30-32], and in particular McGraw, Hoffmann, Harker and Herman [25] and Jenni, Deboer and Achermann [24] showed that the circadian rhythm in sleep is non-existent in the days soon after birth.…”
Section: Resultsmentioning
confidence: 93%
“…It is well understood that the sleep homeostasis in humans are regulated by two independent but synergistic processes (Borbély, 1982;Deboer, 2018): a Clock-dependent circadian process (Process C), controlled by the SCN circadian oscillator, determines the alternation of different sleep propensity (Cremer et al, 2016); and a Sleep-dependent homeostatic process (Process S) that is determined by the prior sleep pressure, which comes from the adenosine buildup in the basal forebrain during wakefulness (Deboer, 2018;Wong et al, 2022). However, due to the immature development of the central nervous system, especially the SCN, Process C and Process S are not stably present in preterm infants or even in term ones (Salzarulo and Fagioli, 1992;Schwichtenberg et al, 2016). As a result, preterm infants experience many sleep and wake episodes within the 24-h period, and those ultradian sleepwake rhythms persist for several months until the Process C and Process S are gradually developed (Mirmiran et al, 2003a;Cremer et al, 2016).…”
Section: Serum Cortisol Levels By Ifamentioning
confidence: 99%